Prevalence and Antimicrobial Susceptibility Patterns of Escherichia coli, Salmonella spp. and Citrobacter freundii Isolated from Ready-to-Eat Fresh Vegetables - Nimmanee, Panjaphorn; Paungmoung, Porntip; Simarub, Chatnapa; Phromrungsawat, Nattiya; Yimnongpho, Pojnicha; Phuttatate, Marisa; Arnamwong, Suthinan; Lumlong, Patsaraphon; Boonchamchoo, Chalinee; Sangchan, Poochisa; Champong, Thanapron; Teetong, Tanpaporn (Asian Health, Science and Technology Reports, 2024)
Thai farmers rely on manure-based fertilizers and irrigation water for plant cultivation, which poses a potential risk of bacterial contamination in their vegetables for sale. The objective of this study was to detect the contamination and antimicrobial susceptibility patterns of Escherichia coli, Salmonella spp. and Citrobacter freundii in 80 samples of ready-to-eat vegetables from various food vendors in Bang Phli district, Samut Prakan Province. E. coli was found in 5 (6.25%) of the vegetable samples and C. freundii was found in 15 (18.75%) of the samples, while Salmonella spp. was not detected in any of the vegetable samples. Most E. coli isolates were found in basil samples whereas most of C. freundii were isolated from sprouts. The results of antimicrobial susceptibility tests of both E. coli and C. freundii against 8 antimicrobial agents using the disk diffusion method revealed that the isolates were susceptible to all antimicrobial agents tested. This study highlights the presence of bacterial contamination in ready-to-eat fresh vegetables, which stems from the use of manure fertilizers. This practice could be a significant source of important enteric pathogens, posing substantial health risks to consumers.